Prediction of the nugget size in resistance spot welding with a combination of a finite-element analysis and an artificial neural network - Afshari, Davood (Materiali in tehnologije, 2014)
The goal of this investigation is to predict the nugget size for a resistance spot weld of thick aluminum 6061-T6 sheets 2 mm. The quality and strength of spot welds determine the integrity of the structure, which depends thoroughly on the nugget size. In this study, the finite-element method and artificial neural network were used to predict the nugget size. Different spot welding parameters such as the welding current and the welding time were selected to be used for a coupled, thermal-electrical-structural finite-element model. In order to validate the numerical results a series of experiments were carried out and the nugget sizes were measured. The results obtained with the finite-element analysis were used to build up a back-propagation, artificial-neural-network model for the nugget-size prediction. The results revealed that a combination of these two developed models can accurately and rapidly predict the nugget size for a resistance spot weld.
Keywords: spot welding; uporovno varjenje; resistance spot weld; uporovni točkasti zvar; velikost področja pretalitve; nugget size; finite-element analysis; analiza končnih elementov; artificial neural networks; umetne nevronske mreže; aluminijeve zlitine; aluminium alloy; aluminum alloys